Total Lactic Acid Bacteria, Antioxidant Activity, and Acceptance of Herbal Soyghurt with Addition of Red Ginger (Zingiber officinale var Rubrum) - Rustanti, Ninik; Prasetyo, Agung Dwi (Nutri-Sains: Jurnal Gizi, Pangan dan Aplikasinya, 2019)
This study aims to determine the effect of red ginger on total lactic acid bacteria, antioxidant activity and acceptance of herbal soyghurt. This study used the addition of red ginger concentration of 0%, 2% and 4% in soyghurt. The total lactic acid bacteria were calculated using Total Plate Count (TPC) method and antioxidant activity test was analyzed by DPPH (2,2-diphenyl-1-picrylhydrazyl) method. The acceptance testing was performed by hedonic test. The addition of red ginger affected antioxidant activity and acceptance test in terms of taste, flavor, and color. The highest antioxidant activity in soyghurt with 4% red ginger is 11.36 ± 1.73%. The addition of red ginger has no effect on the total lactic acid bacteria and soyghurt texture. Soyghurt with 2% red ginger is the best of the acceptance test. It has an antioxidant activity of 10.68 ± 1.13%, and the total lactic acid bacteria 5.00 ± 5.29 x 1016 CFU/ml.